Cost-effectiveness of maintenance niraparib with an individualized starting dosage in patients with platinum-sensitive recurrent ovarian cancer in China - Shi, Yin; Xiao, Di; Li, Shuishi; Liu, Shao; Zhang, Yu (Frontiers in Pharmacology, 2023)
Objective: Niraparib improved survival in platinum-sensitive recurrent ovarian cancer (PSROC) patients versus routine surveillance, accompanied by increased costs. Based on the NORA trial, we evaluated for the first time the cost-effectiveness of maintenance niraparib with individualized starting dosage (ISD) in China. Methods: A Markov model was developed to simulate the costs and health outcomes of each strategy. The total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were measured. One-way and probabilistic sensitivity analysis were performed to estimate model robustness. Scenario analyses were also conducted. Results: Compared to routine surveillance, niraparib additionally increased QALYs by 0.59 and 0.30 in populations with and without germline BRCA (gBRCA) mutations, with incremental costs of $10,860.79 and $12,098.54, respectively. The ICERs of niraparib over routine surveillance were $18,653.67/QALY and $39,212.99/QALY. At a willingness-to-pay (WTP) threshold of $37,488/QALY, the ISD enhanced the likelihood of cost-effectiveness from 9.35% to 30.73% in the gBRCA-mutated group and from 0.77% to 11.74% in the non-gBRCA mutated population. The probability of niraparib being cost-effective in the region with the highest per capita Gross Domestic Product (GDP) in China was 74.23% and 76.10% in the gBRCA-mutated and non-gBRCA mutated population, respectively. Niraparib was 100% cost-effective for National Basic Medical Insurance beneficiaries under the above WTP thresholds. Conclusions: Compared to routine surveillance, the ISD of niraparib for maintenance treatment of PSROC is cost-effective in the gBRCA-mutated population and more effective but costly in the non-gBRCA mutated patients. The optimized niraparib price, economic status, and health insurance coverage may benefit the economic outcome.